Characteristics of Mystical Experience Bl. Dorothy of Montau Based on Historical Sources of Master Johannes of Marienwerder - Kowalczyk, Marta (Studia Warmińskie, 2014)
Johannes of Marienwerder presented Dorothy’s revelations and the story of her life in the trilogy comprising of: Liber de vita venerabilis – 237 chapters telling about the childhood, the marriage, raising children, pilgrimages and spiritual experiences; Apparitiones seu liber de festis – containing her sacred visions received on holidays of the liturgical year and Septililium – concluding 7 treaties about mystical graces received by Dorothy and about her confessions of sins. In the centre of her spiritual life is Jesus Christ. An Eucharist, frequent accepting the Holy Communion, the confession and the contemplative prayer are the essence. Dorothea’s feast day is celebrated on 25 June.